Estimation of patient effective doses in PET/CT- 18F-Sodium Fluoride examinations. (December 2021) - Alnaaimi, Meshari; Sulieman, Abdelmoneim; Tamam, Nissren; Alkhorayef, Mohammed; Alduaij, Musa; Mohammedzein, Talal; Alomair, Othman I.; Alashban, Y.; Salah, H.; Abd-Elghany, Amr A.; Omer, Hiba; Bradley, D.A.
Abstract: The positron emitters ( 18 F-Sodium Fluoride (NaF)) and X-rays used in Positron emission tomography (PET) combined with computed tomography (PET/CT) imaging have a high radiation dose, which results in a high patient dose. The present research intends to determine the radiation dose and risks associated with PET/CT- 18F-Sodium fluoride examinations in patients. The 18F–NaF PET/CT was used to investigate the doses of 86 patients. Patient exposure parameters and ImPACT software were used to calculate mean effective doses. The administered activity of 185 MBq (5.0 mCi) per procedure has a mean and range based on the patient's BMI (BMI). The range of patient effective doses per procedure was found to be 4–10 mSv, with a radiation risk of 1 × 10 −5 per procedure. Patient doses are determined by the patient's size, scanner type, imaging protocol, and reconstruction method. For further dose reduction, proper justification and radiation dose optimization is required. Highlights: Effective doses were estimated for patients undergoing PET/CT procedures. CT contributed 66.7% to patient cumulative effective doses (mSv) while ( 18 F–NaF, PET) contributed 33.3%. Patients dose optimization is recommended during PET/CT examinations.